2017
DOI: 10.1186/s12903-016-0331-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of oral manifestations in children and adolescents with cancer submitted to chemotherapy

Abstract: BackgroundOral complications may be observed during chemotherapy and are important side effects that may directly affect the anticancer treatment, even causing septicaemia in some cases. This research was done in order to evaluate changes in oral lesions during follow-up of children and adolescents in chemotherapy at Hospital Estadual Infantil Nossa Senhora da Glória (HEINSG).MethodsThe study design was longitudinal, 45 patients were evaluated and monitored for 1 month after the initiation of chemotherapy. Twe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
0
10

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 22 publications
6
38
0
10
Order By: Relevance
“…In general, CIOM starts with the initial injury to cells by chemotherapy either as a direct DNA damage or as an indirect through the action of reactive oxygen species. Chemotherapy may be reflected on directly toxic to the oral cavity, as it performed by killing cells having high‐mitotic activity, such as the cells that make up the oral mucosa (Velten, Zandonade, & Monteiro de Barros Miotto, M. H., ). In our study, five out of eight patients were classified WHO Grade 2 with ulceration.…”
Section: Discussionmentioning
confidence: 99%
“…In general, CIOM starts with the initial injury to cells by chemotherapy either as a direct DNA damage or as an indirect through the action of reactive oxygen species. Chemotherapy may be reflected on directly toxic to the oral cavity, as it performed by killing cells having high‐mitotic activity, such as the cells that make up the oral mucosa (Velten, Zandonade, & Monteiro de Barros Miotto, M. H., ). In our study, five out of eight patients were classified WHO Grade 2 with ulceration.…”
Section: Discussionmentioning
confidence: 99%
“…Studies reporting on oral conditions among palliative patients are summarized in Table 1. Of the included studies, 16 were quantitative studies [5,[11][12][13][14][15][16][17][18][19][20][21][22][23][24], and 3 were qualitative studies [25][26][27] (Table 2).…”
Section: Characteristics Of Studymentioning
confidence: 99%
“…Out of 19 studies, 13 reported xerostomia or dryness of mouth [5, 11, 14-17, 19, 23-28]. Eight studies reported candidiasis or oral thrush [11,14,16,20,[23][24][25][26]. Six studies reported dysphagia or swallowing difficulties [15, 17-19, 22, 26].…”
Section: Common Oral Conditions Among Palliative Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 A lterações bucais são comuns em pacientes pediátricos oncológicos e se relacionam tanto com variáveis próprias aos mesmos, como a idade, o diagnóstico e o grau de higiene bucal; quanto com o protocolo antineoplásico adotado, isto é, o fármaco utilizado, dose e frequência do tratamento 1 . Tais alterações podem ser diversas: mucosites, xerostomia, infecções bacterianas, fúngicas ou virais 2 .…”
Section: R Bras CI Saúde 23(1):5-14 2019unclassified